The importance of managing cultural change in the succession process within family businesses in the Gauteng area - Hynd, Dale Vaughan (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
The aim of this research was to ascertain the implications and the impact that the succession process would have on the organisational culture of family businesses. In an attempt to answer this, the researcher asked three questions surrounding the succession process and its relationship with organisational culture. The questions related to the extent to which the family business was prepared for change in management; what changes occurred before, during, and immediately after the succession process, and what results these changes had on the organisational culture. Family businesses account for a large proportion of the national and global market activities, and so it is imperative that attention be paid to any problems they may experience. As it is, family businesses have difficulty in successions, with roughly one third of first generation family businesses surviving the succession process. It is the aim of this research to explore the contribution organisational culture has in the large failure rate of succession with family businesses. When successors enter into the organisation, they bring with them different perspectives on managerial issues suggesting that a change in leadership style will occur as a result of a succession. In answering the research questions, the researcher embarked on a two-phase research methodology utilising a quantitative and qualitative process. This triangulation process incorporates a self-administrated survey questionnaire, and six in-depth interviews. The survey questionnaire and interview schedules were structured using a combination of elements obtained from Harris's (1998) and Levinson's (1972). The survey data was analysed using various statistical methods, predominantly a Factor Analysis, where as Abstract iii the interviews were analysed using a theme retrieval process. The two processes were combined to yield the results. The findings of the research conclude that through the introduction of the successor in the change process, a new leadership style is introduced into the business. The new leader changes policies, practices and procedures, which are related to organisational climate and are the tangible aspects of organisational culture. Altering the climate essentially alters the culture, which may result in anxiety within the organisation and lead to tension. If these issues are not addressed, they may result in the demise of family businesses.
Keywords: Family-owned business enterprises -- South Africa; Family-owned business enterprises -- Succession; Corporate culture -- South Africa